Kontribusi Artificial Intelligence terhadap Kualitas Argumentatif dan Koherensi Paragraf Karya Ilmiah: Systematic Literature Review - Ananda Lailatul Kholifa; Mahfudliyah; Fara Dila Affarani Putri; Imron Fauzi (Yayasan Al-Afif, 2026)
The rapid dvelopment of artifical intelligence (AI) has significanly influenced academic writing, particularly in argument construction and paragraph coherence. This study aims to examine the contribution of AI to argumentative quality and paragraph coherence in academic writing throught a systematic literature review. Data he were collected from peeriviewed articles published whitin the last five years, primarily from scopus indexed journal accessed throught google scholar. The study employed the Prisma fromework to select relevant literature base on inclusion and exclusion criteria, followes by thematic synthesis analysis. The findings reveal that AI assisted writing tools improve argumentative clatrity, idea organization and paragraph coherence by supporting structured argument development and revision processes. However, excessive dependence on AI may weaken critical reasoning skills. This study concludes that responsible and pedagogically guide AI integration can enhance academic writing quality while maintaining students critical and analytical thinking.